Quantitative study on the influence of foundation valley shape on the behaviour of concrete cut-off walls. (April 2022) - Wen, Lifeng; Cao, Weifeng; Li, Yanlong; Liu, Yunhe; Zhou, Heng
Abstract: Concrete cut-off walls are the main seepage control measures for the alluvial foundation of earthen dams. Its mechanical behaviour, which is affected by many factors, is complicated, in which foundation valley shape is one of the main factors. To analyse the influence of the foundation valley shape on the behaviour of the cut-off walls quantitatively, this study defines the foundation valley width coefficient μ, foundation valley steepness coefficient δ and foundation valley asymmetric coefficient γ . A series of numerical calculations on the cut-off wall behaviour with different foundation valley shape parameters was performed on the basis of a core earthen dam. The influence of the foundation valley shape was studied quantitatively by combining it with the numerical results and measured data of the case histories. The behaviour difference between ordinary concrete and plastic concrete cut-off walls was also discussed. Results indicate that the cut-off wall mainly experiences bending deformation. Large tensile stress occurs near the interface between the cut-off wall and the bedrock. The plastic concrete cut-off wall can effectively reduce the tensile stress. The foundation valley width affects the wall behaviour through the bedrock arching effect. μ  = 1.5 can be used as the critical value to distinguish the wide and narrow valley foundation. When δ  > 1.0, the cut-off wall is subjected to large tensile and shear stresses near the contact part of the wall and bedrock. The foundation valley asymmetry causes uneven deformation and large tensile stress on the cut-off wall near the steeper bank slope.